2017
DOI: 10.1080/09712119.2017.1358628
|View full text |Cite
|
Sign up to set email alerts
|

The microbial pH-stable exogenous multienzyme improved growth performance and intestinal morphology of weaned pigs fed a corn–soybean-based diet

Abstract: The present study investigated the effects of dietary supplementation of multienzyme preparation on growth performance, apparent total tract digestibility (ATTD) of nutrients, and gut health of weaned pigs. A total of 240 weaned pigs (initial body weight: 7.3 ± 0.7 kg) were randomly allotted to five treatments on the basis of body weight. The dietary treatments included a corn-soybean meal (SBM)-based diet supplemented with 0 (control), 0.025, 0.050%, 0.075%, or 0.10% multienzyme preparation. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Previous study conducted with weaning pigs reported that applications of NSP-degrading enzymes such as mixtures of glucanase and xylanase significantly altered the production of SCFA and the profiles of gut-associated microflora in weaning pigs [38]. Similarly, Kim et al [39] reported that the inclusion of multi-enzymes in the weaning diet modulated ileum and cecum microflora by increasing the count of Lactobacillus spp. and decreasing the count of E. coli.…”
Section: Intestinal Microfloramentioning
confidence: 95%
“…Previous study conducted with weaning pigs reported that applications of NSP-degrading enzymes such as mixtures of glucanase and xylanase significantly altered the production of SCFA and the profiles of gut-associated microflora in weaning pigs [38]. Similarly, Kim et al [39] reported that the inclusion of multi-enzymes in the weaning diet modulated ileum and cecum microflora by increasing the count of Lactobacillus spp. and decreasing the count of E. coli.…”
Section: Intestinal Microfloramentioning
confidence: 95%
“…To evaluate the small intestinal villus height and crypt depth, on d 28, intestinal samples from euthanized pigs (1 male and 1 female) in each pen were collected. For each intestinal sample, three cross-sections were prepared after staining with azure A and eosin using standard paraffin embedding procedures [13]. A total of 10 intact, well-oriented crypt-villus units were selected in triplicate for each intestinal cross-section.…”
Section: Small Intestinal Morphologymentioning
confidence: 99%
“…The results support the data of Kim et al., (2017) showing that, compared with control diet, the ADG of growing pigs linearly improved by 8.8% in a two-phase feeding regime when β-mannanase supplemented to the diet. Kim et al. (2018b) reported a linear increase in ADG of weaned pigs fed corn-SBM-based feeds formulated with different levels of β-mannanase.…”
Section: Discussionmentioning
confidence: 98%
“…The concentrations of AA in corn, wheat, and SBM determined in growing pigs was within the range of that were previously reported (NRC, 2012). Several studies showed that NSP has an adverse effect on AA losses (Passos et al., 2015, Cadogan and Choct, 2015, Kim et al., 2018b). Increased AID of AA in diets containing β-mannanase is likely caused by the fact that supplemented β-mannanase decreases the digesta viscosity by hydrolyzing the bonds between mannan units (Shim et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation